2012
DOI: 10.1080/10255842.2012.728589
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of injury severity and pattern sustained by overweight drivers in frontal motor vehicle crashes

Abstract: The objective of this study was to examine the role of body mass and subcutaneous fat in injury severity and pattern sustained by overweight drivers. Finite element models were created to represent the geometry and properties of subcutaneous adipose tissue in the torso with data obtained from reconstructed magnetic resonance imaging datasets. The torso adipose tissue models were then integrated into the standard multibody dummy models together with increased inertial parameters and sizes of the limbs to repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…To examine whether the same mechanism is valid for obese children, the body excursions (head, sternum, and pelvis) were measured to evaluate the association between the levels of injuries and forward body excursions ( Table 4). The body excursions were observed to increase as obesity increased, owing to the momentum effect of greater body mass, which is related to the increase of acceleration-related injury measures (i.e., HIC 15 and CA) and is consistent with the finding from the previous study (17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To examine whether the same mechanism is valid for obese children, the body excursions (head, sternum, and pelvis) were measured to evaluate the association between the levels of injuries and forward body excursions ( Table 4). The body excursions were observed to increase as obesity increased, owing to the momentum effect of greater body mass, which is related to the increase of acceleration-related injury measures (i.e., HIC 15 and CA) and is consistent with the finding from the previous study (17).…”
Section: Discussionsupporting
confidence: 89%
“…Both HIC 15 and CA are acceleration‐based injury measures, whereas N ij and CD are force‐ and deformation‐based ones. Our previous study that examined the injury severity sustained by overweight adult drivers in frontal MVCs found that there is a strong correlation between the acceleration‐based injury measures and forward body excursion. To examine whether the same mechanism is valid for obese children, the body excursions (head, sternum, and pelvis) were measured to evaluate the association between the levels of injuries and forward body excursions (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of injury for occupants with obesity is associated with their increased body mass and the poor belt fit caused by their external body shape . The results of this study are in agreement with several previous field data analyses , cadaver tests , and computational studies , all of which have demonstrated the challenges of managing the additional body mass of high‐BMI occupants. In a frontal crash, having greater soft tissue mass will generate higher energy and force that have to be held by the skeleton.…”
Section: Discussionsupporting
confidence: 89%
“…For example, only a few human models representing occupants with obesity are available in the literature. Kim et al and Turkovich et al developed occupant models with obesity using multibody simulation by adding a facet mesh representing more realistic body shapes of occupants with different BMI levels. However, it is difficult for multibody models to accurately simulate the complex interactions between the seat belt and the adipose tissues in the abdominal area.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies about the association between BMI and polytrauma have focused on whether obesity and its comorbidities predict the mortality rate in obese patients with polytrauma. Recently, analysis of computational models of injury severity and injury pattern revealed a highly significant association of thoracic and pelvic injuries with increasing BMI [5]. However, this analysis was computed using crash-test dummies in simulated motor vehicle crashes as a standardized trauma mechanism, while some body fat may have a cushioning effect and may protect the abdominal organs from blunt trauma [6].…”
Section: Introductionmentioning
confidence: 99%